2009
DOI: 10.1136/sti.2009.038000
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between antibiotic susceptibilities and genotypes in Neisseria gonorrhoeae from different geographical origins: determinants monitoring by real-time PCR as a complementary tool for surveillance

Abstract: Showing a good correlation with phenotypic trends of susceptibility, multiplex real-time PCR assays could be used successfully for prospective epidemiological studies notably by characterising mtrR and penB determinants for their fundamental and complementary roles in increasing the antibiotic resistance. These molecular tools could also provide useful alternative surveillance tools for non-viable strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Staphylococcus aureus was the most frequently cultured organism and the majority (22/23; 95.7%) of isolates were meticillin sensitive, although with the emergence of community-acquired meticillin-resistant S. aureus (MRSA) infections in Cambodia this may change with time [15]. Isolates of Neisseria gonorrhoeae were penicillin and fluoroquinolone resistant but susceptible to ceftriaxone, which is similar to the findings of other eye infection studies from Southeast Asia [16, 17]. The addition of molecular testing increased the spectrum of detectable pathogens, most notably in neonates where 60% of infections were associated with detection of Chlamydia trachomatis DNA.…”
Section: Resultssupporting
confidence: 68%
“…Staphylococcus aureus was the most frequently cultured organism and the majority (22/23; 95.7%) of isolates were meticillin sensitive, although with the emergence of community-acquired meticillin-resistant S. aureus (MRSA) infections in Cambodia this may change with time [15]. Isolates of Neisseria gonorrhoeae were penicillin and fluoroquinolone resistant but susceptible to ceftriaxone, which is similar to the findings of other eye infection studies from Southeast Asia [16, 17]. The addition of molecular testing increased the spectrum of detectable pathogens, most notably in neonates where 60% of infections were associated with detection of Chlamydia trachomatis DNA.…”
Section: Resultssupporting
confidence: 68%
“…In contrast, AST data was reported by one paper for Shigella spp. (Meng et al, 2011), and two papers for N. gonorrhoeae (Khauv et al, 2014;Vernel-Pauillac et al, 2010). Four studies reported isolates from nonhuman populations, specifically, E. coli and NTS.…”
Section: Resultsmentioning
confidence: 99%
“…Two papers reported AST data for N. gonorrhoeae (Supplementary Table S7). One reported ciprofloxacin (93.3%) and penicillin (100%) resistance rates on 15 isolates from Cambodia, as part of a larger multi-country study (Vernel-Pauillac et al, 2010). The other reported AST data for 3GC (0%) and ciprofloxacin (100%) from two isolates (Khauv et al, 2014).…”
Section: Neisseria Gonorrhoeaementioning
confidence: 99%
“…In Cambodia, antimicrobial resistance is a growing concern which has already been documented for Neisseria gonorrhoeae [21], S. aureus [22], Salmonella [23,24], Shigella [23], and Escherichia coli [25]. Nearly 45% of the 20 S. aureus strains isolated by the Kampong Cham Hospital laboratory in 2011 were community acquiredmethicillin resistant S. aureus (MRSA) (Somary N., Personal communication, 2011).…”
Section: Discussionmentioning
confidence: 99%